2008
DOI: 10.1021/ed085p990
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Led Team Learning in General Chemistry: Implementation and Evaluation

Abstract: Peer-led team-learning (PLTL) groups have been implemented in both semesters of the general chemistry series at Washington University. We have adapted the PLTL model to fit into a traditional university structure (classes are large; there are multiple sections with different instructors; and graduate students are teaching assistants in the course) by establishing an optional PLTL program outside the course structure. Using data from the fall semesters of 2003 and 2004, we found that students who participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
132
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(147 citation statements)
references
References 11 publications
5
132
0
1
Order By: Relevance
“…To illustrate, between 1995 and 1997 (before Chem-2-Chem was implemented), the percentages of unsuccessful students are 42-51 %, then when the program is implemented, it is dropped to 21 %. In addition, Hockings et al (2008) examine the effect of the PLTL model on student achievement by using it with traditional course structure. The results show that the model satisfies the needs of the faculty and students, presenting the model as a compulsory part of the course is suitable for a traditional university structure, and the students compulsorily participate.…”
Section: Pltl Implementations In General Chemistry Coursementioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate, between 1995 and 1997 (before Chem-2-Chem was implemented), the percentages of unsuccessful students are 42-51 %, then when the program is implemented, it is dropped to 21 %. In addition, Hockings et al (2008) examine the effect of the PLTL model on student achievement by using it with traditional course structure. The results show that the model satisfies the needs of the faculty and students, presenting the model as a compulsory part of the course is suitable for a traditional university structure, and the students compulsorily participate.…”
Section: Pltl Implementations In General Chemistry Coursementioning
confidence: 99%
“…Since the PLTL was first implemented in chemistry, the majority of the conducted studies has been done in this area, especially conducted in general chemistry (Alger & Bahi, 2004; Ba´ez-Galib et al, 2005;Chan & Bauer, 2015;Drane, Micari, & Light, 2014;Mitchell, Ippolito, & Lewis, 2012) (Liou-Mark, Dreyfuss, & Young, 2010;Loui-Mark & Robbins, 2008) and the findings support the success of the model. In other words, students in the PLTL group receive higher grades (Hockings et al, 2008) and learning in these students has higher retention rate (Drane et al, 2014;Lewis, 2011).Ba 'ez-Galib et al (2005) aim to make general chemistry students be successful at the undergraduate level by preparing an interactive program named Chem2Chem. They prepare a supportive learning environment in which students' positive attitudes and self-confidence are supported to meet their academic and emotional needs without compromising the quality, content, and expectations of the course.…”
mentioning
confidence: 99%
“…Mandatory attendance is recommended. A growing body of research supports the utilization of PLTL with students participating in PLTL consistently outperforming those who did not by a third of a grade point with similar student groups [24,25]. At institutions where PLTL was implemented across the curriculum, student pass rates were seen to increase in General Chemistry by 15% while retaining the level of rigor prevalent in a standard lecture course [26].…”
Section: Mentoringmentioning
confidence: 99%
“…Research in chemistry education has shown that active engagement of the students in the learning process is useful and results in more meaningful learning 1 . The literature reports several interactive teaching methods such as peer-led teaching learning (PLTL) 2 , process-oriented guided inquiry learning (POGIL) 3 , PBL (problem-based learning) 4 , flipped classrooms 5 , etc. We had the opportunity to attend a workshop on the POGIL approach by Kelly Butler (Chestnut Hill College, Philadelphia, USA) at Homi Bhabha Centre for Science Education (HBCSE; TIFR), Mumbai in August 2013.…”
mentioning
confidence: 99%